Sequestered lumbar disc herniation mimicking spinal tumor - Biasi, Pedro Radalle; Mallmann, Adroaldo Baseggio; Crusius, Paulo Sérgio; Seibert, Cláudio Albano; Crusius, Marcelo Ughini; Crusius, Cassiano Ughini; Espanhol, Rafael Augusto; Brunet, Matheus Pintos; Carazzo, Charles André (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2013)
The occurrence of herniated disc simulating diseases in neuroimaging it's an uncommon situation. However, due to changes that occur in sequestered disc fragment, some cases can mimic spinal neoplasms. Thus, we present the case of a female patient, 60 year-old, with left back pain and left leg weakness. Left lower limb presented with strength grade IV, positive 45 degress Lasègue's signal and patellar areflexia. Lumbar spine magnetic resonance imaging (MRI) showed an expansive left centro-lateral lesion at L4-L5 level, hypointense on T1W, hyperintense on T2W, with peripheral contrast uptake, causing compression of the dural sac and L5 nerve root. A hemilaminectomy was performed, with complete excision of the lesion. Histological analisys confirmed discal hernia. Disc herniation is a condition characterized by the displacement of the disc content to the spinal canal, predominantly in the lumbar region, and manifesting as radiculopathy. The fragment sequestration occurs in 30% of the cases and is characterized by loss of continuity with remaining disc. MRI exams generally allow diagnostic confirmation; however, there may be diagnostic confusion with tumors, arachnoid cysts and abscesses. The inflammatory reaction occurred in the disc fragment produces the differences in MRI signal. The fragment is hypointense on T1W, hyperintense on T2W, with peripheral enhancement after contrast. Malignancies and Schwannomas have homogeneous or heterogeneous uptake. The epidural abscess is isointense on T1W and hyperintense on T2W, with homogeneous or peripheral enhancement, similar to discal herniation. Thus, sequestered disc herniation can mimic other space-occupying lesions, being necessary a surgical approach to obtain material for histopathological analysis and diagnostic confirmation.
Keywords: Intervertebral disc displacement; spinal cord neoplasms; nerve sheath neoplasms; lumbar vertebrae